Succeeding with inquiry in science and math classrooms - Marshall, Jeff C., 1965- (ASCD, 2013)
"Thinking critically. Communicating effectively. Collaborating productively. Students need to develop proficiencies while mastering the practices, concepts, and ideas associated with mathematics and science. Successful students must be able to work with large data sets, design experiments, and apply what they're learning to solve real-world problems. Research shows that inquiry-based instruction boosts students' critical thinking skills and promotes the kind of creative problem solving that turns the classroom into an energized learning environment. No matter what your experience with inquiry-based instruction, Succeeding with Inquiry in Science and Math Classrooms will help hone your ability to plan and implement high-quality lessons that engage students and improve learning"--Provided by publisher.